Pre-Translation Text Analysis as an Essential Step to an Effective Translation - Gasparyan, Gayane (Armenian Folia Anglistika, 2020)
Pre-translation text analysis is an integral part of an efficient translation procedure. In fact, it focuses on collecting intra-textual and extra-textual information on the text under translation. Collecting the intra-textual information is mainly based on a thorough analysis of the source text linguistic peculiarities, whereas the extra-textual information focuses basically on the communicative functional properties of both source and target texts. There exist different approaches towards this procedure and the stages of its accomplishment. Nonetheless, it should be noted that they all lead to a broader spectrum of discourse analysis with its intra-textual and extra-textual parameters and give birth to the translation-oriented pragmatic analysis before initiating translation process itself. The article focuses on the interrelation and interaction of all the mentioned types of analysis (pragmatic analysis, discourse analysis, pre-translation analysis) as an essential requirement for a relevant translation.